Use of plants by Myzus persicae in agroecosystems: Potential applications in conservation biological control - Zumoffen, Leticia; Ghiglione, Carla; Signorini Porchiett, Marcelo Lisandro; Salvo, Silvia Adriana (Wiley, 2021)
Myzus persicae (Sulzer) is a highly polyphagous aphid species that attacks several economically important crop plants. Here, trophic webs involving M. persicae, its host plants and its parasitoids were described and quantified in wheat, oat and alfalfa agroecosystems from central Argentina, with special emphasis on the sub‐habitats where interactions occur: crops and adjacent field margins. Three fields cultivated with each crop species and their margins were sampled during three years; aphid abundance and mummification percentage were compared among crop plants and the diverse natural vegetation in the borders. Interactions were described using a quantitative food web approach, and abundance and mummification percentage e data were analysed using a generalized linear model. Four plant species present in the borders (Capsella bursa‐pastori, Rapistrum sp., Melilotus sp. and Trifolium repens) hosted M. persicae and its parasitoids. The alfalfa agroecosystem produced a significantly higher number of aphids than oat and wheat; however, in all cases, crops and borders sustained similar aphid abundance. A total of six Aphidiinae species attacked M. persicae, with no significant differences in the richness of parasitoid species between the borders and the crops, but with significant differences in parasitoid abundance, being higher in the crops. Mummification percentage were higher in crops than in the borders, with Lysiphlebus testaceipes, Aphidius colemani and A. ervi being the most abundant species. Almost 70% of M. persicae individuals were collected from fields borders, which highlights the importance of including these sites in studies of trophic interactions in crop fields.